Advances in Study of Time-Delay Systems and Their Applications: A Second Edition - Libor Pekař (Mathematics)
The delay phenomenon is a common feature of industrial, communication, economic, biological, and similar systems and processes, and it significantly affects their stability and dynamics [...]